Monocytes From Patients With Macrophage Activation Syndrome and Secondary Hemophagocytic Lymphohistiocytosis Are Hyperresponsive to Interferon Gamma - Pascarella, Antonia; Bracaglia, Claudia; Caiello, Ivan; Arduini, Alessia; Moneta, Gian Marco; Rossi, Marianna Nicoletta; Matteo, Valentina; Pardeo, Manuela; De Benedetti, Fabrizio; Prencipe, Giusi (Frontiers in Immunology, 2021)
Objective. To investigate the activation of the IFNγ signalling pathway in monocytes of patients with secondary hemophagocytic lymphohistiocytosis (sHLH)/macrophage activation syndrome (MAS) and to evaluate whether levels of phosphorylated STAT1 represent a biomarker for the identification of patients at early stages of the disease. Methods. Fresh whole blood samples from pediatric patients with active sHLH/MAS, not receiving (n=10) and receiving glucocorticoids (n=14) at time of sampling, were prospectively collected. As disease control groups, patients with active systemic juvenile idiopathic arthritis (sJIA) without MAS, patients with sHLH/MAS in remission and patients with other rheumatic diseases were also sampled. Whole blood cells were left unstimulated or stimulated with increasing concentrations of IFNγ for 10 minutes and the intracellular Tyrosine (701)-phosphorylated STAT1 (pSTAT1) levels were evaluated in monocytes by flow cytometry. Results. Monocytes from untreated sHLH/MAS patients showed significantly higher basal levels of pSTAT1 compared to those observed in monocytes from glucocorticoid-treated sHLH/MAS patients and from all the other disease controls. In addition, a significant increase in responsiveness to IFNγ, as assessed by increased levels of pSTAT1 following ex vivo stimulation, was observed in monocytes from untreated sHLH/MAS patients. pSTAT1 levels in monocytes distinguished patients with sHLH/MAS not treated with glucocorticoids from patients with active sJIA or with other rheumatic diseases [AUC, 0.93; 95% confidence interval 0.85-1.00, p<0.001]. Statistically significant correlations between IFNG mRNA levels in whole blood cells, circulating IFNγ levels and pSTAT1 levels in sHLH/MAS monocytes were found. Conclusion. Our data demonstrating higher basal levels of pSTAT1 as well as a hyperreactivity to IFNγ stimulation in monocytes from patients with sHLH/MAS point to perturbations in the activation of downstream IFNγ signalling pathway as a contributor to the hyperinflammation occurring in these patients. Finally, the observation that glucocorticoids affect pSTAT1 levels in vivo, makes it difficult to consider the measurement of pSTAT1 levels as a biomarker to identify patients at early stages of sHLH/MAS in clinical practice.